Building a dynamic Europe : the key policy debates - Gual i Sole, Jordi (Cambridge University Press, 2004)
This volume offers a timely and authoritative analysis of the key economic policy challenges facing the EU today. Written by leading thinkers in the field, it examines policy reforms in areas such as energy, financial services, macroeconomic policy co-ordination, labour markets and welfare state institutions.